Pengaruh Media Playdough terhadap Kemampuan Motorik Halus Anak - Hilda Riyadhatul Auliya; Sukardi; Baiq Nada Buahana (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
Fine motor skills are important skills that need to be developed in early childhood because they are related to the coordination of small muscles, especially finger movements and eye-hand coordination that support children's readiness in learning activities. However, children's fine motor skills are still not optimally developed so that interesting and fun learning media are needed. This study aims to determine the effect of Playdough media on the fine motor skills of early childhood. This study uses a quantitative approach with an experimental research type using a Static Group Comparison design. The population of this study was all group A children at Pembina Sukamulia State Kindergarten. The sample determination used a saturated sampling technique consisting of an experimental group and a comparison group. The research instrument used an observation sheet that had met the validity and reliability tests. The data analysis technique used descriptive statistics and the Independent Sample T Test. The results showed a t value of 24.099 with a significance value of < 0.001. Thus, it can be concluded that Playdough media has an effect on children's fine motor skills.